Schematy, wzorce tekstowe, gatunki mowy... (O kategoryzacji, kategoriach wypowiedzi językowych i ich modelowaniu) - Bożena Witosz (Przestrzenie Teorii, 2007)
The author, by undertaking the issue of categorisation of linguistic statement draws attention to the diversified terminology referring to the text patterns. The observation of the contents of notions - most frequently used nowadays in the theory of text /discourse - as well as their realm and methodological context, leads to the conclusion that this differentiation has its origins not only in the transformations taking place within theoretical discourse concerning the text (eg. pluralism of methodology, tendencies to integrating formulations etc) but also in inconsistent separation of particular levels of categorisation by the researchers, especially the basic level from those placed above and below the basic one. The author suggests that the genre pattern should be treated as an issue from the basic level of categorisation, as it would enable the creation of typological network, which would be transparent and simultaneously it would portray - in the way most closed to the discourse practice - differentiation of the forms of expression. However, in description of the genre (basic category) it requires taking into consideration features of all levels of the discourse: formal, semantic, pragmatic, cognitive and stylistic.